¿Qué es la contabilidad social y ambiental? (2018)
This article states that the concept of Social and Environmental Accounting has two currents, on the one hand those that recognize it as an application of Accounting Theory in the revelation of social and environmental facts, and on the other those who use the term accounting as a substantive fully dissociated from Accounting Theory. To get to know these two currents of thought, we resorted to the study of documents published by a group of “key informants” that were selected based on their curriculum. The work corresponds to an essay that presents the results obtained from the review, defending the aforementioned classification.